The Relationship between Restorative and Consensual Procedures - Csák Zsolt; Czebe András (STUDIA JURIDICA ET POLITICA JAURINENSIS, 2024)
The paper shows how restorative justice fts in with consensual procedures satisfed with procedural justice based on confession of guilt. In our view, the protection of the interests of victims, the establishment of truthful facts and the enforcement of social justice are all objectives that must guide the legislation and the application of law in the 21st century. Although the Hungarian Code of Criminal Procedure has considerably broadened the combinability of consensual procedures, the dangers of the eclipse of material justice cannot be ignored. More specifcally, the contradiction that the more effective restorative justice is, the more pressure is put on the defendant to participate in it, trading the possibility of total victory for the certainty of avoiding total defeat. And although the institutions of the plea agreement and the confession in the preparatory session may compete with the mediation procedure, the latter is the one that can provide the most complete reparation for the victim.